Den absolutte urets subjekt og dets afkom (Debord, Marx, Badiou, Rancière, Negri) - Bolt, Mikkel (Slagmark - Tidsskrift for idéhistorie, 2018)
THE SUBJETCS OF THE ABSOLUTE WRONG AND ITS OPPSPRING (DEBORD, MARX, BADIOU, RANCIÈRE, NEGRI) The notion of the proletariat as the historical subject has disappeared in radical left-wing theory since the late 1960’s. By comparing Guy Debord and the young Marx’s notion of the proletariat with the later notions of transgressive subjectivities, proposed by Alain Badiou, Jacques Rancière and Antonio Negri respectively, the article analyses a split between ‘interior’ and ‘exterior’ in contemporary Marxist and post-Marxist theory.